2019
DOI: 10.7554/elife.47246
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for dyneinopathies reveals insight into dynein regulation and dysfunction

Abstract: Cytoplasmic dynein plays critical roles within the developing and mature nervous systems, including effecting nuclear migration, and retrograde transport of various cargos. Unsurprisingly, mutations in dynein are causative of various developmental neuropathies and motor neuron diseases. These ‘dyneinopathies’ define a broad spectrum of diseases with no known correlation between mutation identity and disease state. To circumvent complications associated with dynein studies in human cells, we employed budding ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 102 publications
1
47
0
Order By: Relevance
“…We previously showed that a K1475Q dynein mutant exhibits phenotypes much like those described for K1475E ( i.e. , increased single molecule run lengths and cortical localization), and leads to compromised dynein function in cells 34 . Thus, the phi particle is an important, highly conserved conformational state that is used by organisms throughout evolution to ensure appropriate dynein activity.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We previously showed that a K1475Q dynein mutant exhibits phenotypes much like those described for K1475E ( i.e. , increased single molecule run lengths and cortical localization), and leads to compromised dynein function in cells 34 . Thus, the phi particle is an important, highly conserved conformational state that is used by organisms throughout evolution to ensure appropriate dynein activity.…”
Section: Discussionmentioning
confidence: 80%
“…We previously found that a disease-correlated amino acid substitution within the linker domain – the mechanical element responsible for the powerstroke – leads to an increase in single molecule run length 34 . This residue (K1475) is equivalent to one known to stabilize the autoinhibited conformation of human dynein (R1567) 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the consequences on apparent brain development in the patient with TUBA1A G436R (pachygyria, and severe microcephaly associated with postural delay and poor communication abilities), and the strong link between mutations in dynein activity and motor neuron diseases and developmental brain disorders (Bahi-Buisson et al, 2014;Laquerriere et al, 2017;Marzo et al, 2019;Vissers et al, 2010;Willemsen et al, 2012), our data linking disrupted dynein activity with this mutation are not entirely surprising. For example, dynein activity is critical for various aspects of early neuronal development, in part by promoting interkinetic nuclear migration in neuronal progenitors, and in the subsequent migration of the resulting postmitotic neurons (Del Bene et al, 2008;Hu et al, 2013;Tsai et al, 2010).…”
Section: Discussionmentioning
confidence: 77%
“…Bars represent weighted means with weighted standard error of proportion. For panels C and, D, P values were calculated using an unpaired Welch's t test; for panels E -G, statistical significance was determined by calculating Z scores as previously described (Marzo et al, 2019). For all plots, diamonds represent mean values obtained from each independent replicate experiment.…”
Section: The G437r Mutation Leads To Increased Spindle Dynamics and Imentioning
confidence: 99%